2002
DOI: 10.1152/jn.2002.88.3.1533
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Signal-Dependent Noise During Isometric Force Production

Abstract: It has been proposed that the invariant kinematics observed during goal-directed movements result from reducing the consequences of signal-dependent noise (SDN) on motor output. The purpose of this study was to investigate the presence of SDN during isometric force production and determine how central and peripheral components contribute to this feature of motor control. Peripheral and central components were distinguished experimentally by comparing voluntary contractions to those elicited by electrical stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
411
2
24

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 504 publications
(462 citation statements)
references
References 39 publications
25
411
2
24
Order By: Relevance
“…This increase of SD with target force is related to the orderly recruitment of motor units: In order to increase muscle force, larger motor units are recruited (Henneman et al 1965), which produce larger and unfused twitches, resulting in increased force fluctuations (Jones et al 2002). As the resultant force represents the spatial summation of activity from different muscles, each contributing to fluctuations on its own direction of action (Kutch et al 2008), an overall increase in muscle activity modulates task-related and tangential forces similarly (Hong et al 2007;Svendsen and Madeleine 2010) , as observed in Fig.…”
Section: Multidirectional Force Fluctuations and Painmentioning
confidence: 99%
See 1 more Smart Citation
“…This increase of SD with target force is related to the orderly recruitment of motor units: In order to increase muscle force, larger motor units are recruited (Henneman et al 1965), which produce larger and unfused twitches, resulting in increased force fluctuations (Jones et al 2002). As the resultant force represents the spatial summation of activity from different muscles, each contributing to fluctuations on its own direction of action (Kutch et al 2008), an overall increase in muscle activity modulates task-related and tangential forces similarly (Hong et al 2007;Svendsen and Madeleine 2010) , as observed in Fig.…”
Section: Multidirectional Force Fluctuations and Painmentioning
confidence: 99%
“…The SD of force is mainly influenced by the intensity of muscle contraction (Jones et al 2002), and the absence of significant changes in iEMG during pain could explain why no differences in the SD of force were observed across different pain conditions. On the other hand, normalized measures of motor output variability (e.g.…”
Section: Multidirectional Force Fluctuations and Painmentioning
confidence: 99%
“…Despite the fact that the errors are relatively small (under 8%), we do not attribute it to "experimental noise" (cf. Jones et al 2002;Van Beers et al 2004). The discrepancy between the model and experimental data is reflected by the term ϑ(t) in Eq.…”
Section: Sources Of Discrepancy Between Experimental and Model Variancementioning
confidence: 99%
“…Further studies of quick motor actions has led to the emergence of a number of formal models for patterns of motor variability observed during the production of fast discrete movements or force pulses by a single effector (Newell and Carlton 1988;Plamondon and Alimi 1997;Jones et al 2002). The main purpose of the current study has been to develop a model for the production of forces by a redundant motor system based on an earlier model of motor variability during single-joint actions (Gutman and Gottlieb 1992;Gutman et al 1993;Latash and Gutman 1993).…”
Section: Introductionmentioning
confidence: 99%
“…15 from Rothwell et al 1982). The variability in the force output may come from multiple sources, including variability in the centrally generated motor command and motor noise (Jones et al 2002). This suggests that afferent feedback is necessary to recalibrate force output.…”
Section: Force Controlmentioning
confidence: 99%